Management of superficial basal cell carcinoma: focus on imiquimod - Beverly Raasch (Dove Medical Press, 2009)
Beverly RaaschSkin Cancer Research Group, North Queensland Centre for Cancer Research, James Cook University, Queensland, AustraliaAbstract: Superficial basal cell carcinoma comprise up to 25% of all histological sub-types. They are more likely to occur on younger persons and females and although generally more common on the trunk, also occur frequently on the exposed areas of the head and neck especially in areas of high sun exposure. In the last decade, new treatment options such as topical applications that modify the immune response have been trialed for effectiveness in treating these lesions. Imiquimod 5% cream has been shown to stimulate the innate and cell mediated immune system. The short-term success of imiquimod 5% cream in randomized controlled trials comparing different treatment regimes and dosing as a treatment for small superficial basal cell carcinoma (BCC) not on the face or neck is in the range of 82% for 5 times per week application. A high proportion of participants with good response rates to topical treatment (58%–92%) experience local side effects such as itching and burning, less commonly erosion and ulceration, but the proportion of participants ceasing treatment has not been high. To date one long-term study indicates a treatment success rate of 78%–81% and that initial response is a predictor of long-term outcome. Recurrences tend to occur within the first year after treatment. Future research will compare this preparation to the gold standard treatment for superficial BCC – surgical excision.Keywords: superficial basal cell carcinoma, imiquimod, skin cancer